Experiments on astrophysical reactions with low-energy unstable nuclei beams at CRIB. (December 2020) - Yamaguchi, G.; Hayakawa, S.; Ma, N.R.; Shimizu, H.; Yang, L.; Kahl, D.; Abe, K.; Suhara, T.; Iwasa, N.; Kim, A.; Kim, D.H.; Cha, S.M.; et al.
Abstract: Studies on nuclear astrophysics, nuclear structure, and other interests have been performed using the radioactive-isotope (RI) beams at the low-energy RI beam separator CRIB, operated by Center for Nuclear Study (CNS), the University of Tokyo. The elastic resonant scattering is a striking tool to study astrophysical reactions and nuclear clusters. In particular, when it is coupled with a thick target and inverse kinematics, the measurement can be very efficient and even feasible with RI beams. By measuring resonant scattering, we can study the properties of resonant states which could play an important role in the astrophysical reaction, or have an exotic nuclear structure. The 10 Be+ α elastic scattering has been measured at CRIB, and three resonances which are in agreement with the prediction of a linear-chain structure by Suhara-En'yo were observed, giving a strong indication of the existence of such an exotic structure. Measurements based on the indirect technique of the reaction measurement, such as the Trojan horse method, have also been performed at CRIB.